A Quarter Century Effort Yet to Come of Age : A Survey of Power Sector Reforms in Developing Countries - Jamasb, Tooraj; Nepal, Rabindra; Timilsina, Govinda R. (World Bank, Washington, DC, 2015)
It has been more than two decades since the widespread initiation of global power sector reforms and restructuring. However, empirical evidence on the intended microeconomic, macroeconomic, and quality-related impacts of reforms across developing countries is lacking. This paper comprehensively reviews the empirical and theoretical literature on the linkages between power sector reforms, economic and technical efficiency, and poverty reduction. The review finds that the extent of power sector reforms has varied across developing countries in terms of changes in market structures, the role of the state, and the regulation of the sector. Overall, the reforms have improved the efficiency and productivity in the sector among many reforming countries. However, the efficiency gains have not always reached the end consumers because of the inability of sector regulators and inadequate regulatory frameworks. Reforms alleviate poverty and promote the welfare of the poor only when the poor have access to electricity. From a policy-making perspective, this implies that the reforms need to be supplemented with additional measures for accelerating electrification to help the poor.